2013
DOI: 10.1001/2013.jamaophthalmol.361
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic Retinopexy for the Repair of Primary Rhegmatogenous Retinal Detachment

Abstract: To assess the outcome and risk factors for failure of pneumatic retinopexy (PR) in eyes with primary rhegmatogenous retinal detachment (RRD).Methods: Data of patients who underwent PR for the repair of primary RRD, from January 1, 2000, through June 30, 2011, were retrieved from medical records and retrospectively analyzed. Patients with a follow-up time of less than 4 months were contacted and invited for examination. Patients with less than 2 months of follow-up were excluded. Successful cases (attached reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 19 publications
(28 reference statements)
4
38
1
1
Order By: Relevance
“…These rates were chosen because previously reported studies have a wide range of success. Studies have reported a range from 60–65% primary success, 3,8,1618 75% primary success, 15,19 and even higher rates, up to 90–95%. 14 …”
Section: Resultsmentioning
confidence: 99%
“…These rates were chosen because previously reported studies have a wide range of success. Studies have reported a range from 60–65% primary success, 3,8,1618 75% primary success, 15,19 and even higher rates, up to 90–95%. 14 …”
Section: Resultsmentioning
confidence: 99%
“…BCVA ≥ 20/40 was attained in 85% in SOS eyes compared to 71% of eyes requiring additional surgery (P = . 19).…”
Section: Anatomic and Visual Outcomesmentioning
confidence: 99%
“…This result was confirmed by Mudvari et al (2009). Recently, Fabian et al (2013) found no significant difference in visual acuity outcomes between successful PR cases and those with only one additional operation, but significantly worse outcomes in the cases requiring two or more additional operations. However, their results were not stratified by procedure type.…”
Section: Discussionmentioning
confidence: 71%